Star wars, the clone wars. The complete season three [videorecording (DVD)]. - Lucas, George, 1944- (Lucasfilm, 2011)
Season three pits the Jedi Knights against Jabba the Hutt, Greedo, and the deadly brother of Sith apprentice Darth Maul! Mystery and adventure await Padawan Ahsoka Tano as she proves her strength as a Jedi with the help of a familiar furry ally, Chewbacca. Includes all 22 episodes.